Indirect Inguinal Hernia Containing a Fallopian Tube and Ovary in a Reproductive Aged Woman. (16th June 2014) - Graul, Ashley; Ko, Emily
Abstract : An indirect inguinal hernia containing an incarcerated fallopian tube and ovary is extremely rare in adult females. The current report describes a woman of reproductive years presenting with an irreducible indirect hernia which required the surgical intervention of a general surgeon as well as counseling regarding future fertility by a gynecologist. The diagnosis was made by physical and sonographic examination and was confirmed by CT scan and surgical intervention. We suggest a multimodel and multidisciplinary approach in order to safely and efficiently preserve ovarian and fertility function in young women who present with an inguinal hernia containing reproductive organs.